Distribution and sources of fallout 137Cs and 239+240Pu in equatorial and Southern Hemisphere reference soils - G. Dicen; G. Dicen; F. Guillevic; S. Gupta; P.-A. Chaboche; P.-A. Chaboche; P.-A. Chaboche; K. Meusburger; P. Sabatier; O. Evrard; C. Alewell (Earth System Science Data)
Past nuclear weapons testing (NWT) and nuclear power plant (NPP) accidents have resulted in the ubiquitous deposition of radionuclides in the environment. These fallout radionuclides (FRNs) are considered the privileged markers (“golden spikes”) of the Anthropocene stratigraphic layers. Their deposition in the 1950s coincided with the “Great Acceleration”, which is characterized by large-scale shifts in the Earth's systems, including increased land-use change and soil degradation. Among the FRNs deposited globally, 137Cs has been the most commonly used to assess soil erosion and/or the chronology of sediment deposition, while 239+240Pu is an alternative soil erosion tracer and chronological marker that has been increasingly used due to a number of advantages.